PKM Mendemonstrasikan Daun Pisang dalam Tradisi Dole-dole Bagi Masyarakat di Kelurahan Kadolomoko Kota Bau bau - Laxmi Laxmi; Erens E. Koodoh; Zainal Zainal; I Subandrio; Sarlan Adi Jaya; Rahel Anggun Nita (Indo Publishing, 2026)
This Community Service Program (PKM) was conducted to demonstrate the role of banana leaves in the Dole-dole tradition among the community of Kadolomoko Village, Baubau City. The program was implemented by demonstrating how banana leaves—which grow abundantly in the vicinity of Kadolomoko Village—are used in the Dole-dole tradition, a life-cycle ceremony for the Buton people. The demonstration process involved the following stages: collecting the leaves, sorting those suitable for use in the ritual ceremony, and selecting the leaves to be used in the Dole-dole phase. The results of the PKM indicate that banana leaves are known to serve three primary functions for the Kadolomoko community: (1) as a mat for the baby during the swaddling ceremony, anointed with coconut oil, turmeric, and lime as a symbol of protection; (2) as a wrapper for ritual food (saba), a traditional Buton dish symbolizing patience and tranquility; and (3) as a cover for the poluka (copper pot) containing symbolic foods including eggs, glutinous rice, cassava, taro, bananas, and fish. The use of banana leaves reflects the collective cognitive knowledge system of the Buton community, which connects people, nature, and cultural traditions that have been preserved from generation to generation. Bhisa Bhawine, as the lead figure alongside a team of faculty and students in this PKM project, demonstrated the use of banana leaves to participants whose children follow the dole-dole tradition, helping them understand that the leaves serve not merely as a food flavoring, an ingredient in cake-making, or for preparing meat, but as a central element in the dole-dole tradition for children’s health and the observance of the life cycle rituals of the Buton people.